Suppressing piracy in the early eighteenth century : pirates, merchants and British imperial authority in the Atlantic and Indian oceans - Wilson, David (Maritime historian) (The Boydell Press, 2021)
Shows how Britain and its empire was not a strong centralised imperial state and that it was only through manifold activities taking place in different colonial centres with varied colonial arrangements that the surge in piracy in this period was contained and reduced.